Mast Cells and Innate Lymphoid Cells: Underappreciated Players in CNS Autoimmune Demyelinating Disease - Brown, Melissa A.; Weinberg, Rebecca B. (Frontiers in Immunology, 2018)
Multiple sclerosis (MS) and its mouse model EAE, experimental autoimmune encephalomyelitis, are autoimmune CNS inflammatory diseases. As a result of a breakdown in the relatively impermeable blood brain barrier (BBB) in affected individuals, myelin-specific CD4+ and CD8+ T cells gain entry into the immune privileged CNS and initiate myelin, oligodendrocyte and nerve axon destruction. However, despite the absolute requirement for T cells, there is increasing evidence that innate immune cells also play critical amplifying roles in disease pathogenesis. By modulating the character and magnitude of the myelin-reactive T cell response and regulating BBB integrity, innate cells affect both disease initiation and progression. Two classes of innate cells, mast cells and innate lymphoid cells, have been best studied in models of allergic and gastrointestinal inflammatory diseases. Yet there is emerging evidence that these cell types also exert a profound influence in CNS inflammatory disease. Both cell types are residents within the meninges and can be activated early in disease to express a wide variety of disease-modifying cytokines and chemokines. In this review, we discuss how mast cells and innate lymphoid cells can have either disease-promoting or -protective effects on Multiple sclerosis and other CNS inflammatory diseases and how sex hormones may influence this outcome. These observations suggest that targeting these cells and their unique mediators can be exploited therapeutically.